2018
DOI: 10.3390/su10092965
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Modelling and Artificial Neural Network Inspired Prediction of Waste Generation Rates of Hospitality Industry: The Case of North Cyprus

Abstract: This study was undertaken to forecast the waste generation rates of the accommodation sector in North Cyprus. Three predictor models, multiple linear regression (MLR), artificial neural networks (ANNs) and central composite design (CCD), were applied to predict the waste generation rate during the lean and peak seasons. ANN showed highest prediction performance, specifically, lowest values of the standard error of prediction (SEP = 2.153), mean absolute error (MAE = 1.378) and highest R 2 value (0.998) confirm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Azarmi et al compared three predictive models, i.e., MLR, CCD and ANN, predicting the mean waste generation rates from hotels in North Cyprus, based on the input data, including: type of waste, season, type of accommodation and waste management practice. In the course of the research, it was noted that ANN indicated the highest efficiency (standard error of prediction SEP = 2.153, mean absolute error MAE = 1.378 and R 2 = 0.998) [14]. Similar results were obtained by Azadi and Karimiashni, who compared ANN and MLR while predicting seasonal municipal solid waste generation for Fars province, Iran.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Azarmi et al compared three predictive models, i.e., MLR, CCD and ANN, predicting the mean waste generation rates from hotels in North Cyprus, based on the input data, including: type of waste, season, type of accommodation and waste management practice. In the course of the research, it was noted that ANN indicated the highest efficiency (standard error of prediction SEP = 2.153, mean absolute error MAE = 1.378 and R 2 = 0.998) [14]. Similar results were obtained by Azadi and Karimiashni, who compared ANN and MLR while predicting seasonal municipal solid waste generation for Fars province, Iran.…”
Section: Introductionsupporting
confidence: 70%
“…The modern waste management models found in the literature incorporate expert systems [10][11][12], evolutionary programming [13], artificial neural networks [14][15][16][17][18], multiple linear regression (MLR) [14,19,20] central composite design (CCD) [14] and various combination of these tools. It is, however, artificial neural network (ANN) modeling that has been on the forefront due to its distinct advantages over other methods, such as the clear network model, uncomplicated implementation and the quality of performance [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Accommodation sector in particular needs to adapt themselves and adopt new strategies as well as utilizing new methods and trends. It was estimated that the amount of total waste generated by hotels during the lean season amounted to 2010.5 kg/day in north Cyprus, in which the share of large hotels was (66.7%), followed by medium size hotels (19.4%), and guesthouses (2.6%) [22]. Therefore, this study adheres to tackling the issue of sustainability which resonates with statement that: "The United Nations Sustainable Development Goals of the 2030 Agenda for Sustainable Development indicate the need to rethink the current economic growth ideology in the context of social and environmental needs in development" [2] (p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, most of the studies have been carried out using the Singe Regression Analysis (SRA) approach, however, ANN, FL, and Multiple Regression Analysis (MRA) and are also quite commonly used. It can be noted that ANN-based models in the case of MSW management are used from different perspectives: ro analyze MSW related data [27] or capture disposal trend [28], to develop predictive models together with other machine learning (ML) or to optimization algorithms [29], deep learning approaches [30] for forecasting waste generation [31] and classification tasks based on image recognition [32].…”
Section: Introductionmentioning
confidence: 99%